2019
DOI: 10.1136/tsaco-2018-000262
|View full text |Cite
|
Sign up to set email alerts
|

Resuscitative endovascular balloon occlusion of the aorta (REBOA): indications: advantages and challenges of implementation in traumatic non-compressible torso hemorrhage

Abstract: BackgroundResuscitative endovascular balloon occlusion of the aorta (REBOA) is regaining popularity in the treatment of traumatic non-compressible torso bleeding. Advances in invasive radiology coupled with new damage control measures assisted in the refinement of the technique with promising outcomes. The literature continues to have substantial heterogeneity about REBOA indications, applications, and the challenges confronted when implementing the technique in a level I trauma center. Scoping reviews are exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 81 publications
2
42
0
2
Order By: Relevance
“…This may have resulted from a bias that may have occurred during collection of data or due to the small amount of data (total number of patients was 54). In other studies, there is no evidence that males have a higher risk of occurrence of complications [13,15,17]. The judgment of this phenomenon should be withheld until more data is accumulated.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This may have resulted from a bias that may have occurred during collection of data or due to the small amount of data (total number of patients was 54). In other studies, there is no evidence that males have a higher risk of occurrence of complications [13,15,17]. The judgment of this phenomenon should be withheld until more data is accumulated.…”
Section: Discussionmentioning
confidence: 95%
“…Two of them had multiple organ (spleen, liver, and lung) injuries, and the other had solitary lung injury. REBOA is indicated mostly in patients with life-threatening hemorrhagic injuries below the diaphragm [12], and the performance of REBOA in thoracic trauma patients with or without other torso injuries has been debated [13]. Ordoñez et al [14] suggested that the combination of RE-BOA and ERT could be useful in patients with non-compressible torso hemorrhage secondary to penetrating chest trauma in their 7-case series report.…”
Section: Discussionmentioning
confidence: 99%
“…Ordoñez et al [18], in their seven-case series report, suggested that the combination of REBOA and emergent resuscitative thoracotomy could be useful in pa-tients with non-compressible torso hemorrhage secondary to penetrating chest trauma. However, we performed REBOA only in patients with an injury below the diaphragm because REBOA is usually indicated in patients with injuries below the diaphragm [19], and performing REBOA in thoracic trauma patients with or without other torso injuries is debated [11]. Failure of the procedure was defined as when the RE-BOA balloon was not located in the desired target Zone during the first procedure.…”
Section: Discussionmentioning
confidence: 99%
“…REBOA involves temporary placement of a balloon in the aorta to block the proximal portion of the bleeding site [3,[11][12][13]. REBOA is less invasive compared to OACC and may provide similar physiological results [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation